12 New twinning mechanism in hexagonal-close-packed structured biomaterials. (March 2019) - Jiang, S; Jiang, ZT; Deng, Y; Wang, MG
Abstract : Background: Magnesium and titanium alloys are important biomaterials due to their good biocompatibility. However, the twinning mechanism in them remains obscure. Methods: The lattice structure of {10⥘2} twin boundaries in a deformed magnesium alloy was examined by using high-resolution transmission electron microscopy and compared with a previously established model. Results: A type of atomic cluster with a specified structure was discovered to appear at the distorted lattice area of the twin boundary. The orientation of the atomic clusters shows a clear rotation tendency from the parent to the twin. Conclusion: The twinning in hexagonal-close-packed metals was confirmed to be induced by the reorientation of the atomic clusters. Acknowledgements: Supported by the National Natural Science Foundation of China (Grant No. 51301215), Talent Project of Chongqing University of Arts and Sciences (Grant No. R2014CJ04 and 2017RXC24) and the Scientific and Technological Research Program of Chongqing Municipal Education Commission (Grant No. KJ1601117) Chongqing Research Program of Basic Research and Frontier Technology (NO. cstc2017jcyjBX0051 and cstc2014jcyjA50033).